PAINTER: Ingress Traffic Engineering and Routing for Enterprise Cloud Networks - Koch, Thomas; Yu, Shuyue; Agarwal, Sharad; Beckett, Ryan; Katz-Bassett, Ethan (SIGCOMM, 2023)
Enterprises increasingly use public cloud services for critical business needs. However, Internet protocols force clouds to choose between high availability and performance, reducing the speed at which clouds can respond to network problems, the range of solutions they can provide, and deployment resilience. To overcome this limitation, we present PAINTER, a system that takes control over which routes are available and which are chosen to the cloud by leveraging edge proxies. PAINTER efficiently advertises BGP prefixes, exposing more concurrent routes than existing solutions to improve latency and resilience. Compared to existing solutions, PAINTER reduces path inflation by 75% while using a third of the prefixes of other solutions, avoids 20% more path failures, and chooses ingresses from the edge at finer time (RTT) and traffic (per-flow) granularities, enhancing our agility.